Preparation of polycyclic aromatic hydrocarbon-based pre-sodium modification agent and application of polycyclic aromatic hydrocarbon-based pre-sodium modification agent in hard carbon negative electrode
By pre-sodiumizing the hard carbon anode of sodium ion batteries using polycyclic aromatic hydrocarbon pre-sodiumizing agent, the problems of poor reversibility of hard carbon anode on sodium ion storage and low initial Coulomb efficiency were solved, and significantly improved electrochemical performance and Cyclic stability.
Patent Information
- Application Number
- CN202411322404.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-11
AI Technical Summary
The problem of poor reversibility of sodium ion battery storage of hard carbon anode and low initial Coulomb efficiency.
The PAHs-Na-ether pre-sodium agent is prepared by reacting with an ether solvent and a sodium metal to prepare a pre-sodium agent for the pre-sodiumization treatment of the hard carbon negative electrode.
The initial Coulomb efficiency of the hard carbon negative electrode was significantly improved to 94.5%, and the capacity was maintained in more than 120 cycles, improving the cycle stability and safety of the battery.
Smart Images

Figure CN119419269A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery negative electrodes, and specifically relates to the preparation of a pre-sodiumized hard carbon negative electrode, and in particular to a high initial efficiency and long cycle electrochemical sodium storage system. Background Art
[0002] Sodium-ion batteries (SIBs) have broad application prospects in large-scale energy storage. Hard carbon (HC) is the current mainstream negative electrode material for sodium-ion batteries, although it has the advantages of low cost, stable structure and performance. During the first charge and discharge, defects on the HC surface and oxygen-containing functional groups cause excessive decomposition of the electrolyte, resulting in irreversible capacity and low initial coulombic efficiency (ICE), which in turn affects the battery cycle life. This has become one of the bottlenecks restricting the development of SIBs. Therefore, the development of a simple pre-sodium technology is expected to promote the practical application of SIBs. Summary of the invention
[0003] The purpose of the present invention is to solve the problem of poor reversibility and low initial coulombic efficiency of sodium ion storage in hard carbon negative electrode of sodium ion battery, and provide a preparation of pre-sodiumization agent based on polycyclic aromatic hydrocarbons and its application in hard carbon negative electrode. 2 The planar π-conjugated disc-shaped molecules composed of hybrid carbon have excellent charge transfer ability and can react with various alkali metals to form alkali metal organic solutions with strong reducing properties. However, PAHs usually have extremely low redox potentials (~0.1V vs. Na + / Na), which can easily lead to excessive sodiumization of the negative electrode and damage the electrode structure. The induction and conjugation effects in the electronic effect can regulate the chemical properties and reaction behaviors of the molecules, and then regulate the rate and selectivity of the chemical reaction. Therefore, by grafting functional groups with different electrical properties (such as -CN, -F, -CH3, etc.) on PAHs molecules, the reducibility of the pre-sodiumization agent is selectively regulated, and the formation of a highly stable interfacial film is assisted to avoid damage to the internal structure of the negative electrode and excessive sodiumization.
[0004] The technical solution of the present invention is:
[0005] The preparation method of a polycyclic aromatic hydrocarbon pre-sodiumizing agent comprises the following preparation steps:
[0006] (1) Preparation of a pre-sodium agent: polycyclic aromatic hydrocarbons (PAHs) and an ether solvent are continuously stirred at room temperature for 5 to 10 minutes, and after being uniformly mixed, a 0.25 to 0.5 mol / L PAHs-ether solution is obtained; metallic sodium (Na) and PAHs are added to the PAHs-ether solution at a molar ratio of 1.5 to 2:1, and the mixture is fully stirred for 1.5 to 2 hours, followed by standing for 20 to 30 minutes, to finally obtain a PAHs-Na-ether pre-sodium agent;
[0007] (2) Preparation of hard carbon negative electrode: Commercial hard carbon material, conductive carbon black and binder were mixed in water at a mass ratio of 8:1:1 and stirred for 2-3 hours. After the mixture was made into a uniform slurry, it was coated on the aluminum foil current collector and dried in a forced air drying oven at 80-100°C for 8-10 hours. Finally, the dried electrode was cut into discs with a diameter of 10 mm using a cutting machine.
[0008] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode is soaked in PAHs-Na-ether pre-sodiumization agent for pre-sodiumization, and the reaction time is 10 to 20 min and then taken out; the soaked working electrode is rinsed with ethylene glycol dimethyl ether and placed in a vacuum oven at 70°C for 15 to 30 min until completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0009] In step (1), the polycyclic aromatic hydrocarbon is one of naphthonitrile, naphthyl acetonitrile, methyl biphenyl, methyl phenanthrene or dimethyl biphenyl; and the ether solvent is one of diethylene glycol dimethyl ether, tetrahydrofuran or ethylene glycol dimethyl ether.
[0010] In step (2), the conductive carbon black may be one of SuperP, Ketjen black or acetylene black; and the binder may be one of sodium carboxyethyl cellulose or sodium alginate.
[0011] In step (3), the water and oxygen contents in the reaction environment are respectively less than 0.01 ppm; and the pressure setting range of the vacuum drying is -0.1 to 0.05 MPa.
[0012] The present invention also provides the use of a pre-sodiumized hard carbon negative electrode in a sodium ion battery, and the method is as follows:
[0013] (4) Battery assembly: Commercial hard carbon material, conductive carbon black (superP) and sodium methyl cellulose (CMC-Na) were mixed in water / ethanol at a mass ratio of 8:1:1 to form an electrode slurry, which was then scraped onto the aluminum current collector with a thickness of 150-200 μm and dried in a drying oven at 80-100°C for 8-10 hours. After drying, the electrode was cut into circular pieces with a diameter of 10 mm. Finally, a two-electrode system was formed with sodium metal in a glove box, and the battery assembly model was a CR2032 button cell.
[0014] The advantages and beneficial effects of the present invention are:
[0015] The preparation process is simplified, the equipment is simple, the repeatability is good, and there is no need for excessive subsequent treatment, which is suitable for large-scale production. First, compared with the solid pre-sodium system, the Na + can be dispersed more evenly in the solvent, which helps Na +Better pre-embedded into the negative electrode material. The hard carbon negative electrode is chemically pre-sodiumized in a strongly reducing solution, and Na is released through the redox reaction on the surface of the material. + . Since the reduction potential of the negative electrode material is reduced, the electrolyte will be decomposed to form a uniform and thin solid electrolyte interface (SEI), which helps to improve the cycle stability and safety of the battery. Electrochemical tests show that the prepared hard carbon negative electrode has a significantly improved initial coulombic efficiency (94.5%) and can be stably cycled for more than 120 times without capacity decay, showing excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the cycling performance of the hard carbon negative electrode at a current density of 100 mA / g.
[0017] Figure 2 The cycling performance of the pre-sodiumized hard carbon negative electrode at a current density of 100 mA / g.
[0018] Figure 3 These are the first cycle charge and discharge curves of different hard carbon negative electrodes at a current density of 100 mA / g.
[0019] Figure 4 It is a comparative diagram, (a) is the first cycle charge and discharge curve of the hard carbon negative electrode after pre-sodiumization in biphenyl-Na-DME at a current density of 100 mA / g; (b) is the cycle performance of the hard carbon negative electrode after pre-sodiumization in biphenyl-Na-DME. DETAILED DESCRIPTION
[0020] Example 1
[0021] (1) Preparation of pre-sodium agent: 0.025 mol of 1-naphthonitrile and 100 mL of ethylene glycol dimethyl ether (DME) solvent were continuously stirred at room temperature for 5 min to obtain 0.25 mol / L 1-naphthonitrile-DME solution; 0.0375 mol of metallic sodium (Na) was added to the 1-naphthonitrile-DME solution and stirred thoroughly for 1.5 h. The solution was then allowed to stand for 20 min to finally obtain 1-naphthonitrile-Na-DME pre-sodium agent.
[0022] (2) Preparation of hard carbon negative electrode: Commercial hard carbon material, acetylene black and sodium alginate binder were mixed in water at a mass ratio of 8:1:1 and stirred for 3 hours. After forming a uniform slurry, it was scraped onto the aluminum foil current collector and placed in an 80°C forced air drying oven for 10 hours. Finally, the dried electrode was cut into discs with a diameter of 10 mm using a cutting machine.
[0023] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode was immersed in 1-naphthonitrile-Na-DME pre-sodiumization agent for pre-sodiumization, and the reaction time was 20 min; the electrode was taken out and the working electrode was rinsed with DME after immersion, and placed in a vacuum oven at 70 ° C for 20 min until it was completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0024] Example 2
[0025] (1) Preparation of pre-sodium agent: 0.1 mol of 4-methylbiphenyl was continuously stirred in 500 mL of tetrahydrofuran (THF) solvent at room temperature for 8 min to obtain a 0.5 mol / L 4-methylbiphenyl-THF solution; 0.2 mol of metallic sodium (Na) was added to the 4-methylbiphenyl-THF solution and stirred thoroughly for 2 h. The solution was then allowed to stand for 30 min to obtain a 4-methylbiphenyl-Na-THF pre-sodium agent.
[0026] (2) Preparation of hard carbon negative electrode: Commercial hard carbon material, Ketjen black and sodium carboxyethyl cellulose binder were mixed in water at a mass ratio of 8:1:1 and stirred for 2.5 hours. After forming a uniform slurry, it was scraped onto the aluminum foil current collector and placed in a 100°C forced air drying oven for 8 hours. Finally, the dried electrode was cut into discs with a diameter of 10 mm using a cutting machine.
[0027] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode was soaked in 4-methylbiphenyl-Na-THF pre-sodiumization agent for pre-sodiumization, and the reaction time was 15 min; the electrode was taken out and the working electrode was rinsed with THF after soaking, and placed in a vacuum oven at 70 ° C. and kept for 30 min until completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0028] Example 3
[0029] (1) Preparation of pre-sodium agent: 0.03 mol of 4,4-dimethylbiphenyl was continuously stirred in 100 mL of diethylene glycol dimethyl ether (G2) solvent at room temperature for 10 min to obtain 0.3 mol / L 4,4-dimethylbiphenyl-G2 solution; 0.045 mol of metallic sodium (Na) was added to the 4,4-dimethylbiphenyl-G2 solution and stirred thoroughly for 1 h. Then the solution was allowed to stand for 20 min to finally obtain 4,4-dimethylbiphenyl-Na-G2 pre-sodium agent.
[0030] (2) Preparation of hard carbon negative electrode: Commercial hard carbon material, conductive carbon black (superP) and sodium alginate were mixed in water at a mass ratio of 8:1:1 and stirred for 3 hours. After forming a uniform slurry, it was scraped onto the aluminum foil current collector and placed in a 100°C forced air drying oven for 8 hours. Finally, the dried electrode was cut into discs with a diameter of 10 mm using a cutting machine.
[0031] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode was immersed in 4,4-dimethylbiphenyl-Na-G2 pre-sodiumization agent for pre-sodiumization, and the reaction time was 30 min; the electrode was taken out and the working electrode was rinsed with G2 after immersion, and placed in a vacuum oven at 70 ° C and kept for 20 min until it was completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0032] Example 4: Battery Assembly
[0033] First, in a glove box with water and oxygen content <0.01ppm respectively, the pre-sodiumized hard carbon negative electrode and sodium metal are used to form a two-electrode system, and the battery assembly model is CR2032 button battery. Sodium hexafluorophosphate (NaPF6) is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) (volume ratio of 1:1:1) as the electrolyte; a glass fiber with a diameter of 16mm is used as the diaphragm, and a metal sodium sheet with a diameter of 14mm is used as the counter electrode. The entire assembly process is completed in a glove box with an argon atmosphere, and the voltage test range is 0.01~2.5V (vs.Na / Na + ).
[0034] Figure 1 The figure is the cycle performance diagram of the hard carbon negative electrode at a current density of 100mA / g. The test results show that the cycle performance of the commercial hard carbon negative electrode in the ester electrolyte fluctuates and the capacity gradually decays. This is attributed to the unstable formation of SEI, which affects the Na + Continuous insertion / extraction.
[0035] Figure 2 The cycling performance of the pre-sodiumized hard carbon anode at a current density of 100 mA / g. As can be seen from the figure, after a one-step pre-sodiumization treatment, the cycling stability has been significantly improved.
[0036] Figure 3 The first cycle charge and discharge curves of different hard carbon negative electrodes at a current density of 100mA / g. By comparison, it can be seen that the hard carbon negative electrode after pre-sodium treatment can increase the ICE to 94.5%, effectively reducing the irreversible capacity of the first cycle.
[0037] Comparative Example
[0038] (1) Preparation of pre-sodium agent: 0.06 mol of biphenyl was continuously stirred in 300 mL of ethylene glycol dimethyl ether (DME) solvent at room temperature for 8 min to obtain a 0.3 mol / L biphenyl-DME solution; 0.12 mol of metallic sodium (Na) was added to the biphenyl-DME solution and stirred thoroughly for 2 h. The solution was then allowed to stand for 20 min to obtain a biphenyl-Na-DME pre-sodium agent.
[0039] (2) Preparation of hard carbon negative electrode: Commercial hard carbon material, SuperP and sodium alginate binder were mixed in water at a mass ratio of 8:1:1 and stirred for 3 hours. After forming a uniform slurry, it was scraped onto the aluminum foil current collector and placed in a 90°C forced air drying oven for 8 hours. Finally, the dried electrode was cut into discs with a diameter of 10 mm using a cutting machine.
[0040] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode was immersed in biphenyl-Na-DME pre-sodiumization agent for pre-sodiumization, and the reaction time was 20 min; the electrode was taken out and the working electrode was rinsed with DME after immersion, and placed in a vacuum oven at 70 ° C. and kept for 20 min until completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0041] Figure 4 (a) is the first cycle charge and discharge curve of different hard carbon negative electrodes at a current density of 100mA / g. By comparison, it can be seen that the hard carbon negative electrode treated with biphenyl-Na-DME pre-sodiumization can increase the ICE from 70% to 92%. At the same time, the open circuit voltage corresponding to the initial discharge of the first cycle is significantly reduced, proving that the negative electrode is reduced by the pre-sodiumization agent to a certain extent. (b) is the cycle performance of the hard carbon negative electrode after pre-sodiumization in biphenyl-Na-DME. It can be seen from the figure that in this system, although the ICE is improved to a certain extent, the reaction activity of biphenyl in the pre-sodiumization agent is too high, which causes the electrode structure to be destroyed, resulting in insufficient cycle stability. Therefore, in the present invention, polycyclic aromatic hydrocarbon pre-sodiumization agents based on different substituents can achieve better pre-sodiumization effects.
Claims
1. A preparation method based on a polycyclic aromatic hydrocarbon pre-sodium agent, characterized in that The method comprises the following preparation steps: (1) Preparation of pre-sodium agent: polycyclic aromatic hydrocarbons (PAHs) and ether solvent are continuously stirred at room temperature for 5 to 10 minutes, and after being uniformly mixed, a PAHs-ether solution is obtained; metallic sodium Na is added to the PAHs-ether solution and stirred thoroughly for 1.5 to 2 hours, and then allowed to stand for 20 to 30 minutes, and finally a PAHs-Na-ether pre-sodium agent is obtained; (2) Preparation of hard carbon negative electrode: Commercial hard carbon material, conductive carbon black and binder were mixed in water at a mass ratio of 8:1:1, stirred for 2-3 hours, and after being made into a uniform slurry, it was scraped on the aluminum foil current collector and placed in a blast drying oven at 80-100°C for 8-10 hours. Finally, the dried electrode was cut into discs with a diameter of 10 mm using a cutting machine; (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode is soaked in PAHs-Na-ether pre-sodiumization agent for pre-sodiumization, and the reaction time is 10 to 20 min and then taken out; the soaked working electrode is rinsed with ethylene glycol dimethyl ether and placed in a vacuum oven at 70°C for 15 to 30 min until completely dry to obtain a pre-sodiumized hard carbon negative electrode.
2. The preparation method of the pre-sodiumizing agent according to claim 1, wherein In step (1), the molar concentration of polycyclic aromatic hydrocarbons in the ether solvent is 0.25-0.5 mol / L, and the molar ratio of metallic sodium to polycyclic aromatic hydrocarbons is 1.5-2:
1.
3. The preparation method of the pre-sodiumizing agent according to claim 1, wherein The polycyclic aromatic hydrocarbon is one of naphthonitrile, naphthyl acetonitrile, methyl biphenyl, methyl phenanthrene or dimethyl biphenyl; the ether solvent is one of diethylene glycol dimethyl ether, tetrahydrofuran or ethylene glycol dimethyl ether.
4. The preparation method of the pre-sodiumizing agent according to claim 1, wherein In step (2), the conductive carbon black is one of SuperP, Ketjen black or acetylene black; and the binder is one of sodium carboxyethyl cellulose or sodium alginate.
5. The preparation method of the pre-sodiumizing agent according to claim 1, wherein In step (3), the water and oxygen contents in the reaction environment are respectively less than 0.01 ppm; and the pressure setting range of the vacuum drying is -0.1 to 0.05 MPa.
6. A pre-sodiumizing agent based on polycyclic aromatic hydrocarbons, characterized in that: It is prepared by the method according to any one of claims 1 to 5.
7. Use of the polycyclic aromatic hydrocarbon pre-sodiumization agent according to claim 6 in a hard carbon negative electrode of a sodium ion battery.
Citation Information
Patent Citations
Sodium ion battery negative electrode pre-sodium modification method, obtained negative electrode material and sodium ion battery
CN109546134A
Modified alkali metal ion battery negative plate as well as preparation method and application thereof
CN113130853A
Pre-sodium-modified graphene negative pole piece, preparation method thereof and sodium ion battery
CN113178548A
Pre-sodium-modified negative pole piece as well as pre-sodium-modified method and application thereof
CN115249795A
Method for intercalating alkali metal ions into carbon electrodes
US5443601A
Cited By
Positive / negative electrode coupled pre-sodium-modified sodium ion battery and construction method thereof
CN121618065A
A sodium-ion battery with positive / negative coupling pre-sodiation and a construction method thereof
CN121618065B